(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current research aims to develop a theoretical framework that combines what has been written about Test-Wiseness in an integrated cognitive structure that combines its most important axes: its concept, ongenesis, components, and strategies. The results showed that the most important of which is that the concept of experiential wisdom did not receive the necessary attention and care by those interested and educational decision-makers, especially those concerned with the decisions of measuring and evaluating the educational process in the State of Kuwait, and the negligence and ignorance of this important variable was proven by educational decision-makers, as it was necessary for those in charge of the educational process. The research is to peruse and keep pace with modern and contemporary educational trends, especially in the field of educational measurement and evaluation, and seek the help of specialists. A number of recommendations were presented, the most important of which is the need to work on spreading and strengthening the culture: test-wiseness among students of various educational stages and educational groups, especially those with special needs; holding workshops and training for teachers and students aimed at equipping them and developing their skills and strategies of experiential wisdom; the need to include curricula with diverse thinking skills in content. The research reviews the educational measurement and evaluation system currently in use. Also, it presents a number of research proposals, the most important of which is building and developing training programs for experiential wisdom strategies, measuring their effectiveness in various educational stages in public education (public and private) and university education in the State of Kuwait, and studying the relationship between experiential wisdom and intelligence in light of the theory of multiple intelligences.